2013
DOI: 10.1111/jnc.12349
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic neurotoxicity ofS‐ethylN,N‐dipropylthiocarbamate (EPTC), molinate, andS‐methyl‐N,N‐diethylthiocarbamate (MeDETC) inCaenorhabditis elegans

Abstract: Epidemiological studies corroborate a correlation between pesticide use and Parkinson’s disease (PD). Thiocarbamate and dithiocarbamate pesticides are widely used and produce neurotoxicity in the peripheral nervous system. Recent evidence from rodent studies suggests that these compounds also cause dopaminergic (DAergic) dysfunction and altered protein processing, two hallmarks of PD. However, DAergic neurotoxicity has yet to be documented. We assessed DAergic dysfunction in Caenorhabditis elegans (C. elegans)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…Additionally, MND-induced changes in the hTTR PTPM pattern were mostly reversed by NAC. These findings are consistent with previous studies in which NAC supplementation of C. elegans increased the resistance to environmental stressors4445. Additionally, cell culture based studies have shown that the antioxidant NAC effectively protected against MND-induced oxidative stress4647.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, MND-induced changes in the hTTR PTPM pattern were mostly reversed by NAC. These findings are consistent with previous studies in which NAC supplementation of C. elegans increased the resistance to environmental stressors4445. Additionally, cell culture based studies have shown that the antioxidant NAC effectively protected against MND-induced oxidative stress4647.…”
Section: Discussionsupporting
confidence: 92%
“…The C. elegans strains were propagated at 20 °C on Nematode Growth Medium (NGM) plates or 8 P plates seeded with either Escherichia coli strain OP50 or NA22, respectively. Synchronous L1 populations were obtained by treating worms with an alkaline bleach solution (1% NaClO and 0.25 M NaOH)45. L1 larvae were placed on OP50-seeded NGM plates after hatching and experiments were performed using L4 stage nematodes unless otherwise noted.…”
Section: Methodsmentioning
confidence: 99%
“…Results of recent work demonstrate thiocarbamate pesticides to be toxic to DA neurons and implicate these pesticides as potential risk factors for PD [22]. The thiocarbamate molinate was found to an inhibitor of ALDH, and more specifically, molinate and its sulfoxide and sulfone metabolites were found to inactivate human ALDH2 [23,24].…”
Section: Environmental Agents and Da Metabolismmentioning
confidence: 99%
“…(Caenorhabditis Genetics Center, CGC). To obtain a synchronous population, worms were treated with an alkaline bleach solution (1% NaOCl and 0.25 M NaOH) as described 39 . Synchronized L1 worms were placed on OP50-seeded NGM plates after hatching and experiments were performed using L4 stage nematodes.…”
Section: Methodsmentioning
confidence: 99%